Evaluation of the literature surrounding shared decision-making in elective rhinological surgery: A scoping review - Karadaghy, Omar A.; Vukas, Rachel R.; Villwock, Jennifer A. (Auris, nasus, larynx, 2021)
[1] review all studies utilizing SDM in the treatment of chronic rhinosinusitis (CRS) [2], increase awareness of otolaryngologists to shared decision-making, and [3] provide a framework for its incorporation into research and clinical practice. systematic search was performed in November 2019 using PubMed/MEDLINE 1947-, CINAHL Complete 1937-, the Cochrane Library, ClinicalTrials.gov, and Web of Science Core Collection (SCI-EXPANDED, SSCI, A&HCI, ESCI) 1900-. All databases were searched from their inception through the date of search. Studies were eligible if they involved a discussion of SDM in the management of CRS. Studies were excluded if they lacked original patient data or outcomes of interest. Identified studies were screened by title/abstract, followed by full-text review. PRISMA guidelines were strictly followed. in total, 416 articles met screening criteria. Six were eligible for full text review. Only one study – an expert panel of the framework for the presurgical treatment of CRS - pertained to SDM. While this study mentions that SDM is a critically important piece to optimize care quality, it does not directly investigate the effects of SDM in CRS. this review represents a significant negative study that identifies a clear gap in the rhinology literature. Despite the recognized importance of SDM, there have been no interventional studies in the literature to investigate SDM in CRS. This review highlights the need for exploring the role of SDM in rhinological surgery, outlines an overview of SDM and its impact on patient outcomes, and provides a proposed framework for incorporating SDM in research and clinical practice.